PEMIKIRAN KH. M. HASYIM ASYâ€™ARI TENTANG HAK DAN KEWAJIBAN SUAMI ISTRI - Masrokhin; M. Rizki Syahrul Ramadhan (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2023)
â€˜UlamÄ has different opinions about the varians and the technicals the rights and obligations for husband and his wife. In Indonesia, that differences could be find in the literature-work of Indonesianâ€™s â€˜ulamÄ such as á¸Œawâ€™ al-Miá¹£bÄá¸¥ fÄ« BayÄn Aá¸¥kÄm al-NikÄá¸¥, the work of KH. M. Hasyim Asyâ€™ari. Consider to the established of istinbÄá¹ theory in uá¹£Å«l al-fiqh, this research asking question about â€œHow the method of istinbÄá¹ al-aá¸¥kÄm of KH. M. Hasyim Asyâ€™ari in deciding the rights and obligations for husband and his wife?â€ Keywords: Thought, KH. M. Hasyim Asyâ€™ari, Right and Obligation, Husband and Wife Daftar Pustaka Asyâ€™ari, Muhammad Hasyim. 2017. á¸Œawâ€™ al-Miá¹£bÄá¸¥ fÄ« BayÄn Aá¸¥kÄm al-NikÄá¸¥. Jombang: Pustaka Tebuireng _______________________. t.th. RisÄlah Ahl al-Sunnah wa al-JamÄ'ah fÄ« BayÄn al-MusammÄh bi Ahl al-Sunnah wa al-JamÄ'ah. Jombang: Maktabah TurÄth al-IslÄmÄ«. _______________________. t.th. Al-TibyÄn fÄ« al-Nahy 'an MuqÄtha'ah al-Ará¸¥Äm wa al-AqÄrib wa al-IkhwÄn. Jombang: Maktabah TurÄth al-IslÄmÄ«. _______________________. 1415 H. ZiyÄdah Ta'lÄ«qÄt 'alÄ Manáº“Å«mah al-Shaykh â€˜Abd AllÄh YÄsÄ«n al-FÄsuruwÄnÄ«. Jombang: Maktabah al-TurÄth al-IslÄmÄ«. Badawi, Syansuri. 2004.Uá¹£Å«l al-Fiqh. Jombang: Majelis Ilmi Pesantren Tebuireng. Hadziq, Muhammad Ishomuddin. t.th. IrshÄd al-SÄrÄ«. Jombang: Maktabah al-TurÄth al-IslÄmÄ«. __________________________, 1999. KH. Hasyim Asyâ€™ari, Figur Ulama dan Pejuang Sejati. Jombang: Pustaka Warisan Islam. Khuluq, Lathiful. 2018. Tafsir Pemikiran Kebangsaan dan Keislaman Hadratussyaikh KH. M. Hasyim Asyâ€™ari. Jombang: Pustaka Tebuireng. Masrokhin. 2017. Sejarah Hidup Hadratus Syaikh KH. Muhammad Hasyim Asyâ€™ari dalam Supratno, Haris, dkk. Pemikiran Hadratus Syaikh KH. Muhammad Hasyim Asyâ€™ari. Surabaya: Unesa University Press. Palmer, Donald. 2006. Looking at Philosophy: The Unbearable Heaviness of Philosophy Made Lighter. New York: McGraw-Hill. Rusyd, Ibn. t.th. BidÄyah al-Mujtahid wa NihÄyah al-Muqtaá¹£id. Surabaya: Al-Hidayah, SÄbiq, Al-Sayyid. 2009. Fiqh al-Sunnah. Kairo: al-Fatá¸¥ li al-Iâ€™lÄm al-â€˜ArabÄ«. Saebani, Beni Ahmad. 2011. Filsafat Hukum Islam. Bandung: Pustaka Setia. Shahab, Muhammad Asad. 1971. al-â€˜AllÄmah Muá¸¥ammad HÄshim Ashâ€™arÄ« Waá¸iâ€™ Lubnah IstiqlÄl IndÅ«nÄ«siyÄ. Bairut: DÄr al-á¹¢adiq. Al Amin, Habibi. "Guardians Concept in Qur'an Perspective." Shakhsiyah Burhaniyah: Jurnal Penelitian Hukum Islam 6.1 (2021): 95-114. Al Amin, Habibi. "Penciptaan Adam; Mendialogkan TafsiR Marah Labid dengan Teori Keadilan Gender." An-Nuha: Jurnal Kajian Islam, Pendidikan, Budaya Dan Sosial 1.1 (2014): 17-44. Al Amin, Habibi. "Tafsir Sufi LataÃ¢â‚¬â„¢ if al-Isyarat." SUHUF 9.1 (2016): 59-77. Zuhayli Wahbah, 1985, al-Fiqh al-Islam wa Adillatuhu, Damasqus: Dar al-Fikr. Taufiqurrahman, Zaky Fajar, and Habibi Al Amin. "Desain Pembelajaran Literasi Kitab Kuning Melalui Metode Sorogan dalam Meningkatkan Pemahaman Agama Islam." Syntax Literate; Jurnal Ilmiah Indonesia 6.2 (2021): 1467-1474.